A first-in-human, open-label, dose-escalation and dose-expansion phase I study to evaluate the safety, tolerability, pharmacokinetics/pharmacodynamics, and antitumor activity of QL1604, a humanized anti–PD-1 mAb, in patients with advanced or metastatic solid tumors - Huang, Zhiyu; Xu, Yanjun; Hong, Wei; Gong, Lei; Chen, Kaiyan; Qin, Jing; Xie, Fajun; Wang, Feng; Tian, Xin; Meng, Xiangrui; Feng, Wenlei; Li, Lingyan; et al. (Frontiers in Immunology, 2023)
Background QL1604 is a humanized immunoglobulin G4 monoclonal antibody against programmed cell death protein 1. This first-in-human, open-label phase I study aimed to investigate the safety and tolerability and to identify the recommended doses of QL1604 for future studies. Pharmacokinetics/pharmacodynamics (PK/PD) and preliminary antitumor activity were also assessed. Methods Patients with advanced or metastatic solid tumors who failed or had no standard therapies available were recruited. In the dose-escalation phase, patients were treated with QL1604 at 0.3 mg/kg, 1 mg/kg, 3 mg/kg, and 10 mg/kg intravenously once every 2 weeks (Q2W) in an accelerated titration with a traditional 3 + 3 design, followed by a dose-expansion phase at 3 mg/kg Q2W, 3 mg/kg once every 3 weeks (Q3W), 10 mg/kg Q2W and a fixed dose of 200 mg Q3W. Dose-limiting toxicities (DLTs) were assessed during the first 28 days after the first dose of study drug. Adverse events (AEs) were graded per National Cancer Institute Common Terminology Criteria for Adverse Events version 5.0, and antitumor activity of QL1604 was evaluated by investigators on the basis of Response Evaluation Criteria in Solid Tumors version 1.1. Results A total of 35 patients with advanced or metastatic solid tumors were enrolled. DLTs were reported in one patient at the dose level of 3 mg/kg Q2W (grade 3 immune-mediated myositis and myasthenia gravis), and maximum tolerated dose was not reached. The most frequent treatment-related AEs (≥10%) were fatigue (37.1%), anemia (22.9%), increased blood thyroid-stimulating hormone (17.1%), increased aspartate aminotransferase (AST) (17.1%), increased alanine aminotransferase (ALT) (14.3%), decreased white blood cell (WBC) count (11.4%), rash (14.3%), and pruritus (14.3%). AEs leading to discontinuation of QL1604 occurred in three of the 35 patients (8.6%). Partial responses (PRs) occurred in seven patients, resulting in an objective response rate of 20.0% (7/35). Single dose of QL1604 exhibited a dose-dependent increase in the exposure ranging from 0.3 mg/kg to 10 mg/kg. Mean receptor occupancy (RO) for QL1604 at the dose of 3 mg/kg (Q2W and Q3W) and 200 mg (Q3W) was greater than 80% during cycle 1 after one infusion. Conclusion QL1604 monotherapy exhibited favorable safety, PK, and signal of antitumor activity in patients with advanced or metastatic solid tumors, and the results supported further clinical studies of QL1604. On the basis of the safety, PK, and RO data, the recommended dosage for further clinical trials is 3 mg/kg or a fixed dose of 200 mg given every 3 weeks. Clinical Trial Registration https://classic.clinicaltrials.gov/ct2/show/NCT05649761?term=QL1604&draw=2&rank=1, identifier NCT05649761.